Identifikasi Karakteristik Spasio-Temporal Hujan Ekstrem di Tanjungpinang Menggunakan Google Earth Engine (GEE) - Dian Kharisma Dewi; Sigit Sutikno; Lita Darmayanti (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
In early January 2021, Tanjungpinang was hit by floods due to extreme rainfall intensity, causing the affected communities to suffer material and non-material losses. The flood has occurred from 2011 to 2021. To minimize the impact of flood events, it is necessary to study the characteristics of rainfall both temporally and spatially. This is considered important because with this information the public can anticipate the impact of extreme rainfall at a certain time and location. This study aims to identify the Spatio-temporal characteristics of extreme rainfall in Tanjungpinang City which often causes floods. However, to identify the characteristics of rainfall, long data is needed. This study uses CHIRPS (Climate Hazards InfraRed Precipitation with Station) satellite data because the rainfall observation data at the Raja Haji Fisabilillah station is not available for 2012. The identification results show that the correlation criterion (R) value between rainfall observation data and CHIRPS satellite data is 0.688. This value is interpreted as "strong" to be used as an alternative study data. GEE (Google Earth Engine) as a cloud-based platform is used to identify the spatial and temporal characteristics of extreme rainfall. From the results of temporal identification, it is known that extreme rainfall occurs in January, April, and December. The results of spatial identification indicate that the area that has the highest average maximum rainfalls at the Bukit Bestari District area of 156.60 mm/day. This can then be confirmed by looking at the documentation of flood events that often occur in the area.